The effect of milk on recovery from repeat-sprint cycling in female team-sport athletes - Rankin, P.; Lawlor, M. J.; Hills, F. A.; Bell, P. G.; Stevenson, E. J.; Cockburn, E. (Applied Physiology, Nutrition, and Metabolism, 2018)
The consumption of milk following eccentric exercise attenuates the effects of muscle damage in team-sport athletes. However, participation in team sport involves both concentric-eccentric loading and metabolic stress. Therefore, the aim of this study was to investigate the effects of postexercise milk consumption on recovery from a cycling protocol designed to simulate the metabolic demands of team sport. Ten female team-sport athletes participated in a randomised crossover investigation. Upon completion of the protocol participants consumed 500 mL of milk (MILK) or 500 mL of an energy-matched carbohydrate (CHO) drink. Muscle function (peak torque, rate of force development, countermovement jump, 20-m sprint), muscle soreness and tiredness, serum creatine kinase, high-sensitivity C-reactive protein, and measures of oxidative stress (protein carbonyls and reduced glutathione/oxidized glutathione (GSH/GSSG) ratio) were determined at pre-exercise and 24 h, 48 h, and 72 h postexercise. MILK had a possible beneficial effect in attenuating losses in peak torque (180°/s) from baseline to 24 h (3.2% ± 7.8% vs. -6.2% ± 7.5%, MILK vs. CHO) and a possible beneficial effect in minimising soreness (baseline-48 h; baseline-72 h) and tiredness (baseline-24 h; baseline-72 h). There was no change in oxidative stress following the exercise protocol, though a likely benefit of milk was observed for GSH/GSSG ratio at baseline-24 h (0.369 ×/÷ 1.89, 1.103 ×/÷ 3.96, MILK vs. CHO). MILK had an unclear effect on all other variables. Consumption of 500 mL of milk after repeat sprint cycling had little to no benefit in minimising losses in peak torque or minimising increases in soreness and tiredness and had no effect on serum markers of muscle damage and inflammation.